A Comprehensive Appraisal of the Movements aiming at Fostering Sirah Studies in British India during 1857-1947 CE - Naeem, Hafiz Muhammad; Abdul Hamid, Faisal @ Ahmad Faisal; Yussuf, Ahmad; Raouf, Muhammad Umair (Journal of Al-Tamaddun, 2024)
The study of Sirah stands as a cornerstone of Islamic Studies and related disciplines, having evolved profoundly over the centuries. It offers indispensable historical context and serves as a guiding beacon for Muslims in their faith and conduct. Between 1857 and 1947, Sirah Studies in the Subcontinent underwent a transformative phase that significantly influenced global Sirah scholarship. This period was marked by the emergence of critical works by Orientalists, which spurred robust responses from Muslim scholars in the region, catalyzing the rise of various influential Sirah movements. Traditionally, these movements have been analyzed in isolation, overlooking their collective impact on the evolution of modern Sirah studies. This research aims to bridge that gap by examining the combined effects of these movements, underscoring their unified contributions to the reformation and advancement of Sirah Sciences in the subcontinent.